Aryl piperidine anion exchange membrane containing electron-rich branched monomer as well as preparation method and application of aryl piperidine anion exchange membrane
By introducing electron-rich branched monomers into the alkaline anion exchange membrane, the Π-Π conjugation effect is enhanced and the branched structure is formed, the problem of insufficient swelling and conductivity of existing membrane materials is solved, and high-performance alkaline fuel cells and electrolytic hydrogen-making membrane materials are realized.
Patent Information
- Application Number
- CN202411874835.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The swelling rate and conductivity of existing alkaline anion exchange membranes have not yet been optimized, which affects the performance of alkaline fuel cells and electrolyzed hydrogen production.
By introducing electron-rich branched monomers, the Π-Π conjugation effect of the polymer is enhanced and the branched structure is formed to improve the molecular weight and alkali stability of the polymer, thereby reducing the swelling rate and improving the conductivity.
It achieves high conductivity, low swelling rate and good alkali stability, and improves the performance of alkaline fuel cells and electrolyzed hydrogen production.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alkaline anion exchange membranes, and relates to an arylpiperidine type anion exchange membrane containing electron-rich branched monomers, a preparation method and application thereof. Background Art
[0002] Proton exchange membrane fuel cells (PEMFC) and proton exchange membrane water electrolysis (PEMWE) use precious metal catalysts, which leads to high device costs, while anion exchange membrane (AEMFC) and anion exchange membrane water electrolysis (AEMWE) can use non-precious metal catalysts, which greatly reduces the cost of the device. However, to date, the alkaline stability and battery performance of AEMFC and AEMWE still need to be further improved.
[0003] The key components of AEMFC and AEMWE are membrane electrodes, which are composed of catalysts, ionic polymers and membranes. The membrane material is crucial in the membrane electrode. The membrane plays an important role in transferring hydroxide ions, which is directly related to the battery performance. In addition to high conductivity, the polymer also needs a low swelling rate and good alkaline stability to ensure the stability of the battery. Zhuang Lin et al. reported the development of an oxygen-free main chain polymer QAPPT in Alkaline polymer electrolyte fuel cells stably working at 80℃. The polymer exhibited good alkaline stability due to the absence of aromatic ether bonds. After soaking in 8M NaOH for 10 days, the cation retention rate exceeded 80%. Although significant progress has been made in this field, the swelling rate and conductivity of the membrane material need to be further optimized. The introduction of electron-rich branched monomers into aryl piperidine polymers can not only increase the molecular weight of the polymer by utilizing the abundant π electrons in the monomer to increase the polymer reaction activity, but also form a branched structure to reduce the swelling rate of the polymer, which is beneficial to the long-term stable operation of the battery. Therefore, the study of electron-rich branched monomer aryl piperidine copolymers is of great significance for the structural design and optimization of AEMWE membrane materials. Summary of the invention
[0004] The present invention aims to reduce the swelling rate of an alkaline anion exchange membrane. Since the introduced branched monomer has abundant π electrons, the abundant π electrons can increase the reaction activity of superacid aromatic ketone polymerization and improve the molecular weight of the polymer. The high molecular weight polymer is beneficial to improving the alkali stability of the polymer. Meanwhile, the branched monomer structure contains multiple benzene ring structures, which can increase the π-π conjugation effect in the polymer. The π-π conjugation effect in the polymer is also beneficial to reducing the swelling rate of the polymer. The introduction of branched monomers to form branched centers can also promote the microscopic phase separation of the polymer to enrich ion clusters and improve the electrical conductivity of the polymer, thereby forming an aryl piperidine polymer with high electrical conductivity, low swelling rate and good alkali stability. Therefore, the study of introducing electron-rich branched monomers into aryl piperidine polymers to enhance the π-π conjugation effect and form branched polymers is of great significance for developing high-performance membrane materials suitable for alkaline fuel cells and hydrogen production by water electrolysis.
[0005] The technical solution of the present invention:
[0006] An arylpiperidine anion exchange membrane containing an electron-rich branched monomer has the following structure:
[0007]
[0008]
[0009] Among them, the structure of the electron-rich branched monomer is as follows:
[0010]
[0011] The branching unit structure of the arylpiperidine type polymer containing electron-rich branching monomer is as follows:
[0012]
[0013] Among them, M - For I - Br - , Cl - OH - or HCO3 - ;
[0014] Wherein, n=0.01-0.99, wherein the multi-monomer polymer is formed by copolymerization of terphenyl replacing one or two of the following aromatic structures:
[0015]
[0016] A method for preparing an arylpiperidine anion exchange membrane containing an electron-rich branched monomer, comprising the following steps:
[0017] Step 1: first dissolve p-terphenyl in dichloromethane solvent, stir for 10 minutes, then add N-methyl-4-piperidone and the third monomer A to obtain a mixed solution;
[0018] The molar concentration of N-methyl-4-piperidone in dichloromethane is 1 to 1.2 mol / L;
[0019] The molar ratio of N-methyl-4-piperidone: the third monomer A: p-terphenyl is 1.1: 0.01-0.5: 0.5-0.99;
[0020] The monomer A is 9,10-triphenylene, coronene, hexaphenylbenzene, spiro[fluorene-9,9'-xanthene], spiro[9H-fluorene-9,9'-[9H]thioxanthene], 5λ4-5,5'-spiro[dibenzothiophene](9CI) (CAS No.: 144190-64-7), 1,3,6,8-tetraphenylpyrene, 2,3,6,7,10,11-hexaphenyltriphenylene, 1,3-dithiazole, 2-(4,5-diphenyl-1,3-dithiol-2-ylidene)-4,5-diphenyl (CAS No.: 23780-79-2);
[0021] Step 2: Add trifluoroacetic acid and trifluoromethanesulfonic acid to the mixed solution obtained in step 1 under ice bath conditions, remove the ice bath after 1 hour, react at room temperature for 2-3 hours, add the mixed solution into solvent B for precipitation, and finally wash with water until neutral, and dry in an oven to obtain a three-monomer polymer;
[0022] The molar ratio of p-terphenyl to trifluoromethanesulfonic acid is 1:5-9;
[0023] The molar ratio of p-terphenyl to trifluoroacetic acid is 1:1;
[0024] The solvent B is methanol, ethanol or water;
[0025] Step 3: The three monomer polymers are dissolved in solvent C, potassium carbonate is added after dissolution, iodomethane is added after stirring evenly, and the mixture is reacted at 40° C. in the dark for a period of time; the solution after the reaction is completed is centrifuged, potassium carbonate is removed, and the mixture is poured into solvent D for precipitation, and finally washed with solvent D, filtered, and dried to obtain a quaternary ammonium polymer;
[0026] The molar ratio of the three monomer polymer: methyl iodide: potassium carbonate is 1:1.2-1.5:1-1.5;
[0027] The solvent C is N-methylpyrrolidone or dimethyl sulfoxide;
[0028] The mass concentration of the three-monomer polymer in solvent C is 0.03-0.05 g / mL;
[0029] The precipitation agent D is acetone, ethyl acetate or ether;
[0030] The light-proof reaction time is 36 to 48 hours;
[0031] Step 4: Preparation of polyaryl piperidine type anion exchange membrane: dissolving the quaternized polymer in solvent E, centrifuging to remove impurities after dissolution to obtain a casting solution; casting the casting solution on a glass plate, and drying at a certain temperature to form a membrane; soaking the membrane in 1 mol / L potassium hydroxide solution for 24 to 48 hours, and soaking in deionized water until neutral, thereby obtaining an aryl piperidine type anion exchange membrane;
[0032] The solvent E is N-methylpyrrolidone or dimethyl sulfoxide;
[0033] The mass concentration of the casting solution is 0.015-0.025 g / mL;
[0034] The drying temperature of the film formed by the casting method is 60-80°C and the drying time is 24 hours.
[0035] Beneficial effects of the present invention:
[0036] (1) By introducing branched monomers rich in π electrons, the polymerization activity of aromatic ketones is greatly improved, the molecular weight of the polymer is increased, which is beneficial to reduce the swelling rate and enhance the stability.
[0037] (2) The introduction of branched monomers rich in π electrons can enhance the π-π conjugation of the polymer and reduce the swelling rate of the polymer.
[0038] (3) The introduced branched monomers can play the role of enriching ion clusters and improve the ionic conductivity of the polymer. DETAILED DESCRIPTION
[0039] The specific implementation of the present invention is further described below in conjunction with the technical solution.
[0040] Example 1
[0041] Synthesis of polyaryl piperidine type three-monomer polymer containing 9,10-triphenylene: 2.187g (9.5mmol) of p-terphenyl was added to a 25mL three-necked flask, followed by 5mL of dichloromethane solution, followed by 1.35ml (11mmol) of N-methyl-4-piperidone and 0.114g (0.5mmol) of 9,10-triphenylene. After mechanical stirring for a period of time, 0.75mL (9.8mmol) of trifluoroacetic acid and 8mL (90mmol) of trifluoromethanesulfonic acid were slowly added under ice bath conditions. After 60min, the ice bath was removed and the temperature of the reaction system gradually rose to room temperature. When the reaction solution became very viscous, the reaction solution was poured into methanol to precipitate the crude polymer, which was then washed with deionized water until neutral and dried at 60°C for 24h to obtain the three-monomer polymer material.
[0042] Preparation of quaternary anion exchange membrane: Weigh 2g of three-monomer polymer material and add it to a 100mL single-mouth bottle, then add 50mL DMSO, add 1.669g potassium carbonate and 2.28g iodomethane after dissolution, react at 40℃ in the dark for about 48h, pour the obtained solution into ethyl acetate to precipitate solid powder product, filter and dry, wash with deionized water several times to remove unreacted salt, and dry at 60℃ for 24h to obtain quaternary polymer. Weigh 0.1g of quaternary polymer and dissolve it in 4.5mL DMSO, centrifuge the casting solution and cast it in a glass mold, dry at 60℃ for 48h to obtain a polymer membrane. Soak the polymer membrane in 1mol / L KOH solution at room temperature for 48h, then wash it repeatedly with deionized water and soak it for 48h until it is neutral, and then obtain a quaternary piperidine anion exchange membrane.
[0043] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 145 mS cm at 80°C. -1 The water absorption rate is 50%, the swelling degree is 15%, and the conductivity retention rate is 92% when immersed in 1mol / L NaOH solution at 80℃ for 2000h. The tensile strength of the dry film is 45Mpa. The membrane shows good mechanical strength and alkaline stability. The membrane is assembled into an alkaline fuel cell for testing. At 80℃, the maximum output power is 1.5W / cm 2 . Tested in an alkaline water electrolyte battery, the current reached 4.5A / cm at 80℃ and 2V voltage. 2 .
[0044] Example 2
[0045] Synthesis of coronene-containing polyaryl piperidine-type tetramonomer polymer: 1.842g (8mmol) of p-terphenyl was added to a 25mL three-necked flask, followed by 5mL of dichloromethane solution, followed by 1.35ml (11mmol) of N-methyl-4-piperidone, 0.276g (1.5mmol) of dibenzothiophene and 0.15g (0.5mmol) of coronene. After mechanical stirring for a period of time, 0.75mL (9.8mmol) of trifluoroacetic acid and 8mL (90mmol) of trifluoromethanesulfonic acid were slowly added under ice bath conditions. After 60min, the ice bath was removed and the temperature of the reaction system gradually rose to room temperature. When the reaction solution became highly viscous, the reaction solution was poured into methanol to precipitate the crude polymer, which was then washed with deionized water until neutral and dried at 60°C for 24h to obtain a tetramonomer polymer material.
[0046] Preparation of quaternary anion exchange membrane: Weigh 2g of tetramonomer polymer material and add it to a 100mL single-mouth bottle, then add 50mL DMSO, add 1.669g potassium carbonate and 2.28g iodomethane after dissolution, react at 40℃ in the dark for about 48h, pour the obtained solution into ethyl acetate to precipitate solid powder product, filter and dry, wash with deionized water several times to remove unreacted salt, dry at 60℃ for 24h to obtain quaternary polymer. Weigh 0.1g of quaternary polymer and dissolve it in 4.5mL DMSO, centrifuge the casting solution and cast it in a glass mold, dry at 60℃ for 48h to obtain a polymer membrane. Soak the polymer membrane in 1mol / L KOH solution at room temperature for 48h, then repeatedly wash with deionized water and soak for 48h until neutral, and you can get a quaternary piperidine anion exchange membrane.
[0047] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 152 mS cm at 80°C. -1 The water absorption rate is 40%, the swelling degree is 12%, and the conductivity retention rate is 93% when immersed in 1mol / L NaOH solution at 80℃ for 2000h. The tensile strength of the dry film is 50Mpa. The membrane shows good mechanical strength and alkaline stability. The membrane is assembled into an alkaline fuel cell for testing. At 80℃, the maximum output power is 1.6W / cm 2 . Tested in an alkaline water electrolyte battery, the current reached 5A / cm at 80℃ and 2V voltage. 2 .
[0048] Example 3
[0049] Synthesis of hexaphenylbenzene-containing polyaryl piperidine-type polymer: 2.072g (9mmol) of p-terphenyl was added to a 25mL three-necked flask, followed by 5mL of dichloromethane solution, followed by 1.35ml (11mmol) of N-methyl-4-piperidone and 0.535g (1mmol) of hexaphenylbenzene. After mechanical stirring for a period of time, 0.75mL (9.8mmol) of trifluoroacetic acid and 8mL (90mmol) of trifluoromethanesulfonic acid were slowly added under ice bath conditions. After 60min, the ice bath was removed and the temperature of the reaction system gradually rose to room temperature. When the reaction solution became highly viscous, the reaction solution was poured into methanol to precipitate the crude polymer, which was then washed with deionized water until neutral and dried at 60°C for 24h to obtain a three-monomer polymer material.
[0050] Preparation of quaternary ammonium anion exchange membrane: Weigh 2g of polymer material and add it to a 50mL single-mouth bottle, then add 40mL DMSO, add 1.62g potassium carbonate and 2.28g iodomethane after dissolution, react at 40℃ in the dark for about 48h, pour the obtained solution into ethyl acetate to precipitate solid powder product, filter and dry, wash with deionized water several times to remove unreacted salt, dry at 60℃ for 24h to obtain quaternary ammonium polymer. Weigh 0.1g of quaternary ammonium polymer and dissolve it in 4.5mL DMSO, centrifuge the casting solution and cast it in a glass mold, dry at 60℃ for 48h to obtain a polymer membrane. Soak the polymer membrane in 1mol / L KOH solution at room temperature for 48h, then repeatedly wash with deionized water and soak for 48h until neutral, and you can get a quaternary piperidine anion exchange membrane.
[0051] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 155 mS cm at 80°C. -1 The water absorption rate is 54%, the swelling degree is 18%, and the conductivity retention rate is 90% when immersed in 1mol / L NaOH solution at 80℃ for 2000h. The tensile strength of the dry film is 45Mpa. The membrane shows good mechanical strength and alkaline stability. The membrane is assembled into an alkaline fuel cell for testing. At 80℃, the maximum output power is 1.7W / cm 2 . Tested in an alkaline water electrolyte battery, the current reached 5.3A / cm at 80℃ and 2V voltage. 2 .
[0052] Example 4
[0053] Synthesis of polyaryl piperidine-type polymer containing spiro[fluorene-9,9'-oxanthene]: 1.727g (7.5mmol) of p-terphenyl was added to a 25mL three-necked flask, followed by 5mL of dichloromethane solution, followed by 1.35ml (11mmol) of N-methyl-4-piperidone and 0.831g (2.5mmol) of spiro[fluorene-9,9'-oxanthene], and after mechanical stirring for a period of time, 0.75mL (9.8mmol) of trifluoroacetic acid and 8mL (90mmol) of trifluoromethanesulfonic acid were slowly added under ice bath conditions. After 60min, the ice bath was removed and the temperature of the reaction system gradually rose to room temperature. When the reaction solution became highly viscous, the reaction solution was poured into methanol to precipitate the crude polymer, which was then washed with deionized water until neutral and dried at 60°C for 24h to obtain a three-monomer polymer material.
[0054] Preparation of quaternary ammonium anion exchange membrane: Weigh 2g of polymer material and add it to a 50mL single-mouth bottle, then add 40mL DMSO, add 2g potassium carbonate and 1ml iodomethane after dissolution, react at 40℃ in the dark for about 48h, pour the obtained solution into ethyl acetate to precipitate solid powder product, filter and dry, wash with deionized water several times to remove unreacted salt, dry at 60℃ for 24h to obtain quaternary ammonium polymer. Weigh 0.1g of quaternary ammonium polymer and dissolve it in 4.5mL DMSO, centrifuge the casting solution and cast it in a glass mold, dry at 60℃ for 48h to obtain a polymer membrane. Soak the polymer membrane in 1mol / L KOH solution at room temperature for 48h, then repeatedly wash with deionized water and soak for 48h until neutral, and you can get a quaternary piperidine anion exchange membrane.
[0055] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 150 mS cm at 80°C. -1 The water absorption rate is 52%, the swelling degree is 16%, and the conductivity retention rate is 90% when immersed in 1mol / L NaOH solution at 80℃ for 2000h. The tensile strength of the dry film is 55Mpa. The membrane shows good mechanical strength and alkaline stability. The membrane is assembled into an alkaline fuel cell for testing. At 80℃, the maximum output power is 1.55W / cm 2 In the alkaline water electrolyte battery test, the current reached 4.8A / cm at 80℃ and 2V voltage. 2 .
[0056] Example 5
[0057] Synthesis of polyaryl piperidine-type polymer containing spiro[9H-fluorene-9,9′-[9H]thioxanthine]: 1.957g (8.5mmol) of p-terphenyl was added to a 25mL three-necked flask, followed by 5mL of dichloromethane solution, followed by 1.35ml (11mmol) of N-methyl-4-piperidone and 0.523g (1.5mmol) of spiro[9H-fluorene-9,9′-[9H]thioxanthine]. After mechanical stirring for a period of time, 0.75mL (9.8mmol) of trifluoroacetic acid and 8mL (90mmol) of trifluoromethanesulfonic acid were slowly added under ice bath conditions. After 60min, the ice bath was removed and the temperature of the reaction system gradually rose to room temperature. When the reaction solution became highly viscous, the reaction solution was poured into methanol to precipitate the crude polymer, which was then washed with deionized water until neutral and dried at 60°C for 24h to obtain a three-monomer polymer material.
[0058] Preparation of quaternary ammonium anion exchange membrane: Weigh 2g of polymer material and add it to a 50mL single-mouth bottle, then add 40mL DMSO, add 2g potassium carbonate and 1ml iodomethane after dissolution, react at 40℃ in the dark for about 48h, pour the obtained solution into ethyl acetate to precipitate solid powder product, filter and dry, wash with deionized water several times to remove unreacted salt, dry at 60℃ for 24h to obtain quaternary ammonium polymer. Weigh 0.1g of quaternary ammonium polymer and dissolve it in 4.5mL DMSO, centrifuge the casting solution and cast it in a glass mold, dry at 60℃ for 48h to obtain a polymer membrane. Soak the polymer membrane in 1mol / L KOH solution at room temperature for 48h, then repeatedly wash with deionized water and soak for 48h until neutral, and you can get a quaternary piperidine anion exchange membrane.
[0059] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 156 mS cm at 80°C. -1 The water absorption rate is 48%, the swelling degree is 15%, and the conductivity retention rate is 95% when immersed in 1mol / L NaOH solution at 80℃ for 2000h. The tensile strength of the dry film is 50Mpa. The membrane shows good mechanical strength and alkaline stability. The membrane is assembled into an alkaline fuel cell for testing. At 80℃, the maximum output power is 1.72W / cm 2 In the alkaline water electrolyte battery test, the current reached 5.5A / cm at 80℃ and 2V voltage. 2 .
[0060] Example 6
[0061] Synthesis of polyaryl piperidine type polymer containing 5λ4-5,5'-spiro[dibenzothiophene](9CI)(CAS No.: 144190-64-7): 1.957g (8.5mmol) of p-terphenyl was added to a 25mL three-necked flask, followed by 5mL of dichloromethane solution, followed by 1.35ml (11mmol) of N-methyl-4-piperidone and 0.505g (1.5mmol) of 5λ4-5,5'-spiro[dibenzothiophene](9CI), and after mechanical stirring for a period of time, 0.75mL (9.8mmol) of trifluoroacetic acid and 8mL (90mmol) of trifluoromethanesulfonic acid were slowly added under ice bath conditions. After 60min, the ice bath was removed and the temperature of the reaction system gradually rose to room temperature. When the reaction solution became highly viscous, the reaction solution was poured into methanol to precipitate the crude polymer, which was then washed with deionized water until neutral and dried at 60℃ for 24h to obtain the three-monomer polymer material.
[0062] Preparation of quaternary ammonium anion exchange membrane: Weigh 2g of polymer material and add it to a 50mL single-mouth bottle, then add 40mL DMSO, add 2g potassium carbonate and 1ml iodomethane after dissolution, react at 40℃ in the dark for about 48h, pour the obtained solution into ethyl acetate to precipitate solid powder product, filter and dry, wash with deionized water several times to remove unreacted salt, dry at 60℃ for 24h to obtain quaternary ammonium polymer. Weigh 0.1g of quaternary ammonium polymer and dissolve it in 4.5mL DMSO, centrifuge the casting solution and cast it in a glass mold, dry at 60℃ for 48h to obtain a polymer membrane. Soak the polymer membrane in 1mol / L KOH solution at room temperature for 48h, then repeatedly wash with deionized water and soak for 48h until neutral, and you can get a quaternary piperidine anion exchange membrane.
[0063] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 165 mS cm at 80°C. -1 The water absorption rate is 45%, the swelling degree is 13%, and the conductivity retention rate is 95% when immersed in 1mol / L NaOH solution at 80℃ for 2000h. The tensile strength of the dry film is 50Mpa. The membrane shows good mechanical strength and alkaline stability. The membrane is assembled into an alkaline fuel cell for testing. At 80℃, the maximum output power is 1.8W / cm 2 . Tested in alkaline water electrolyte battery, the current reached 6A / cm at 80℃ and 2V voltage. 2 .
[0064] Example 7
[0065] Synthesis of polyaryl piperidine type polymer containing 1,3,6,8-tetraphenylpyrene: 1.957g (8.5mmol) of p-terphenyl was added to a 25mL three-necked flask, followed by 5mL of dichloromethane solution, followed by 1.35ml (11mmol) of N-methyl-4-piperidone and 0.760g (1.5mmol) of 1,3,6,8-tetraphenylpyrene. After mechanical stirring for a period of time, 0.75mL (9.8mmol) of trifluoroacetic acid and 8mL (90mmol) of trifluoromethanesulfonic acid were slowly added under ice bath conditions. After 60min, the ice bath was removed and the temperature of the reaction system gradually rose to room temperature. When the reaction solution became highly viscous, the reaction solution was poured into methanol to precipitate the crude polymer, which was then washed with deionized water until neutral and dried at 60°C for 24h to obtain a three-monomer polymer material.
[0066] Preparation of quaternary ammonium anion exchange membrane: Weigh 2g of polymer material and add it to a 50mL single-mouth bottle, then add 40mL DMSO, add 2g potassium carbonate and 1ml iodomethane after dissolution, react at 40℃ in the dark for about 48h, pour the obtained solution into ethyl acetate to precipitate solid powder product, filter and dry, wash with deionized water several times to remove unreacted salt, dry at 60℃ for 24h to obtain quaternary ammonium polymer. Weigh 0.1g of quaternary ammonium polymer and dissolve it in 4.5mL DMSO, centrifuge the casting solution and cast it in a glass mold, dry at 60℃ for 48h to obtain a polymer membrane. Soak the polymer membrane in 1mol / L KOH solution at room temperature for 48h, then repeatedly wash with deionized water and soak for 48h until neutral, and you can get a quaternary piperidine anion exchange membrane.
[0067] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 148 mS cm at 80°C. -1 The water absorption rate is 55%, the swelling degree is 17%, and the conductivity retention rate is 92% when immersed in 1mol / L NaOH solution at 80℃ for 2000h. The tensile strength of the dry film is 45Mpa. The membrane shows good mechanical strength and alkaline stability. The membrane is assembled into an alkaline fuel cell for testing. At 80℃, the maximum output power is 1.53W / cm 2 In the alkaline water electrolyte battery test, the current reached 4.7A / cm at 80℃ and 2V voltage. 2 .
[0068] Example 8
[0069] Synthesis of polyaryl piperidine-type polymer containing 2,3,6,7,10,11-hexaphenyltriphenylene: 2.187g (9.5mmol) of p-terphenyl was added to a 25mL three-necked flask, followed by 5mL of dichloromethane solution, followed by 1.35ml (11mmol) of N-methyl-4-piperidone and 0.342g (0.5mmol) of 2,3,6,7,10,11-hexaphenyltriphenylene. After mechanical stirring for a period of time, 0.75mL (9.8mmol) of trifluoroacetic acid and 8mL (90mmol) of trifluoromethanesulfonic acid were slowly added under ice bath conditions. After 60min, the ice bath was removed and the temperature of the reaction system gradually rose to room temperature. When the reaction solution became highly viscous, the reaction solution was poured into methanol to precipitate the crude polymer, which was then washed with deionized water until neutral and dried at 60°C for 24h to obtain the three-monomer polymer material.
[0070] Preparation of quaternary ammonium anion exchange membrane: Weigh 2g of polymer material and add it to a 50mL single-mouth bottle, then add 40mL DMSO, add 2g potassium carbonate and 1ml iodomethane after dissolution, react at 40℃ in the dark for about 48h, pour the obtained solution into ethyl acetate to precipitate solid powder product, filter and dry, wash with deionized water several times to remove unreacted salt, dry at 60℃ for 24h to obtain quaternary ammonium polymer. Weigh 0.1g of quaternary ammonium polymer and dissolve it in 4.5mL DMSO, centrifuge the casting solution and cast it in a glass mold, dry at 60℃ for 48h to obtain a polymer membrane. Soak the polymer membrane in 1mol / L KOH solution at room temperature for 48h, then repeatedly wash with deionized water and soak for 48h until neutral, and you can get a quaternary piperidine anion exchange membrane.
[0071] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 146 mS cm at 80°C. -1 The water absorption rate is 63%, the swelling degree is 20%, and the conductivity retention rate is 92% when immersed in 1mol / L NaOH solution at 80℃ for 2000h. The tensile strength of the dry film is 45Mpa. The membrane shows good mechanical strength and alkaline stability. The membrane is assembled into an alkaline fuel cell for testing. At 80℃, the maximum output power is 1.51W / cm 2 . Tested in alkaline water electrolyte battery, the current reached 5A / cm at 80℃ and 2V voltage. 2 .
[0072] Example 9
[0073] Synthesis of polyaryl piperidine type polymer containing 1,3-dithiazole, 2-(4,5-diphenyl-1,3-dithiol-2-ylidene)-4,5-diphenyl (CAS No.: 23780-79-2): 2.187g (9.5mmol) of p-terphenyl was added to a 25mL three-necked flask, and then 5mL of dichloromethane solution was added, followed by 1.35ml (11mmol) of N-methyl-4-piperidone and 0.254g (0.5mmol) of 1,3-dithiazole, 2-(4,5-diphenyl-1,3-dithiol-2-ylidene)-4,5-diphenyl. After mechanical stirring for a period of time, 0.75mL (9.8mmol) of trifluoroacetic acid and 8mL (90mmol) of trifluoromethanesulfonic acid were slowly added in an ice bath. The ice bath was removed after 60min, and the temperature of the reaction system gradually rose to room temperature. When the reaction solution became highly viscous, the reaction solution was poured into methanol to precipitate the crude polymer, which was then washed with deionized water until neutral and dried at 60° C. for 24 h to obtain a three-monomer polymer material.
[0074] Preparation of quaternary ammonium anion exchange membrane: Weigh 2g of polymer material and add it to a 50mL single-mouth bottle, then add 40mL DMSO, add 2g potassium carbonate and 1ml iodomethane after dissolution, react at 40℃ in the dark for about 48h, pour the obtained solution into ethyl acetate to precipitate solid powder product, filter and dry, wash with deionized water several times to remove unreacted salt, dry at 60℃ for 24h to obtain quaternary ammonium polymer. Weigh 0.1g of quaternary ammonium polymer and dissolve it in 4.5mL DMSO, centrifuge the casting solution and cast it in a glass mold, dry at 60℃ for 48h to obtain a polymer membrane. Soak the polymer membrane in 1mol / L KOH solution at room temperature for 48h, then repeatedly wash with deionized water and soak for 48h until neutral, and you can get a quaternary piperidine anion exchange membrane.
[0075] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 153 mS cm at 80°C. -1 The water absorption rate is 57%, the swelling degree is 18%, and the conductivity retention rate is 88% when immersed in 1mol / L NaOH solution at 80℃ for 2000h. The tensile strength of the dry film is 40Mpa. The membrane shows good mechanical strength and alkaline stability. The membrane is assembled into an alkaline fuel cell for testing. At 80℃, the maximum output power is 1.65W / cm 2 In the alkaline water electrolyte battery test, the current reached 5.5A / cm at 80℃ and 2V voltage. 2 .
[0076] Comparative Example 1
[0077] Synthesis of poly (p-terphenyl piperidine) polymer: 2.303g (10mmol) p-terphenyl was added to a 25mL three-necked flask, followed by 5mL dichloromethane solution, followed by 1.35ml (11mmol) N-methyl-4-piperidone. After mechanical stirring for a period of time, 0.75mL (9.8mmol) trifluoroacetic acid and 8mL (90mmol) trifluoromethanesulfonic acid were slowly added under ice bath conditions. After 60min, the ice bath was removed and the temperature of the reaction system gradually rose to room temperature. When the reaction solution became highly viscous, the reaction solution was poured into methanol to precipitate the crude polymer, which was then washed with deionized water until neutral and dried at 60°C for 24h to obtain the three-monomer polymer material.
[0078] Preparation of quaternary ammonium anion exchange membrane: Weigh 2g of polymer material and add it to a 50mL single-mouth bottle, then add 40mL DMSO, add 2g potassium carbonate and 1ml iodomethane after dissolution, react at 40℃ in the dark for about 48h, pour the obtained solution into ethyl acetate to precipitate solid powder product, filter and dry, wash with deionized water several times to remove unreacted salt, dry at 60℃ for 24h to obtain quaternary ammonium polymer. Weigh 0.1g of quaternary ammonium polymer and dissolve it in 5mL DMSO, centrifuge the casting solution and cast it in a glass mold, dry at 60℃ for 48h to obtain a polymer membrane. Soak the polymer membrane in 1mol / L KOH solution at room temperature for 48h, then repeatedly wash with deionized water and soak for 48h until neutral, and you can get a quaternary piperidine anion exchange membrane.
[0079] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 120 mS cm at 80°C. -1 The water absorption rate is 70%, the swelling degree is 23%, and the membrane is assembled into an alkaline fuel cell for testing. At 80°C, the maximum output power is 1.1W / cm 2 . Tested in alkaline water electrolyte battery, the current reached 2.5A / cm at 80℃ and 2V voltage. 2 .
[0080] Comparative Example 2
[0081] Synthesis of triphenylmethane-containing polyaryl piperidine type polymer: 2.187g (9.5mmol) of p-terphenyl was added to a 25mL three-necked flask, followed by 5mL of dichloromethane solution, followed by 1.35ml (11mmol) of N-methyl-4-piperidone and 0.122g (0.5mmol) of triphenylmethane. After mechanical stirring for a period of time, 0.75mL (9.8mmol) of trifluoroacetic acid and 8mL (90mmol) of trifluoromethanesulfonic acid were slowly added under ice bath conditions. After 60min, the ice bath was removed and the temperature of the reaction system gradually rose to room temperature. When the reaction solution became highly viscous, the reaction solution was poured into methanol to precipitate the crude polymer, which was then washed with deionized water until neutral and dried at 60°C for 24h to obtain a three-monomer polymer material.
[0082] Preparation of quaternary ammonium anion exchange membrane: Weigh 2g of polymer material and add it to a 50mL single-mouth bottle, then add 40mL DMSO, add 2g potassium carbonate and 1ml iodomethane after dissolution, react at 40℃ in the dark for about 48h, pour the obtained solution into ethyl acetate to precipitate solid powder product, filter and dry, wash with deionized water several times to remove unreacted salt, dry at 60℃ for 24h to obtain quaternary ammonium polymer. Weigh 0.1g of quaternary ammonium polymer and dissolve it in 4.5mL DMSO, centrifuge the casting solution and cast it in a glass mold, dry at 60℃ for 48h to obtain a polymer membrane. Soak the polymer membrane in 1mol / L KOH solution at room temperature for 48h, then repeatedly wash with deionized water and soak for 48h until neutral, and you can get a quaternary piperidine anion exchange membrane.
[0083] The test results show that the ion conductivity of the quaternized piperidine anion exchange membrane prepared in this embodiment is 125 mS cm at 80°C. -1 The water absorption rate is 60%, the swelling degree is 21%, and the conductivity retention rate is 85% when immersed in 1mol / L NaOH solution at 80℃ for 2000h. The tensile strength of the dry film is 37Mpa. The membrane shows good mechanical strength and alkaline stability. The membrane is assembled into an alkaline fuel cell for testing. At 80℃, the maximum output power is 1.3W / cm 2 . Tested in alkaline water electrolyte battery, the current reached 3.5A / cm at 80℃ and 2V voltage. 2 .
Claims
1. An arylpiperidine anion exchange membrane containing an electron-rich branched monomer, characterized in that: The structure of the arylpiperidine type anion exchange membrane is as follows: Among them, M - For I - Br - , Cl - OH - or HCO3 - ; Among them, n=0.01~0.
99.
2. The arylpiperidine type anion exchange membrane according to claim 1, characterized in that: The structure of the electron-rich branched monomer is as follows:
3. The arylpiperidine type anion exchange membrane according to claim 1, characterized in that: The branching unit structure of the aryl piperidine polymer containing electron-rich branched monomer is as follows:
4. The arylpiperidine type anion exchange membrane according to claim 1, characterized in that: The p-terphenyl replaces one or two of the following aromatic structures to form a multi-monomer polymer:
5. A method for preparing an arylpiperidine anion exchange membrane containing an electron-rich branched monomer, characterized in that: Here are the steps: Step 1: first dissolve p-terphenyl in dichloromethane solvent, stir for 10 minutes, then add N-methyl-4-piperidone and the third monomer A to obtain a mixed solution; Step 2: Add trifluoroacetic acid and trifluoromethanesulfonic acid to the mixed solution obtained in step 1 under ice bath conditions, remove the ice bath after 1 hour, react at room temperature for 2-3 hours, add the mixed solution into solvent B for precipitation, and finally wash with water until neutral, and dry in an oven to obtain a three-monomer polymer; Step 3: The three monomer polymers are dissolved in solvent C, potassium carbonate is added after dissolution, iodomethane is added after stirring evenly, and the mixture is reacted at 40° C. in the dark for a period of time; the solution after the reaction is completed is centrifuged, potassium carbonate is removed, and the mixture is poured into solvent D for precipitation, and finally washed with solvent D, filtered, and dried to obtain a quaternary ammonium polymer; Step 4: Preparation of polyaryl piperidine type anion exchange membrane: dissolve the quaternary ammonium polymer in solvent E, centrifuge to remove impurities after dissolution to obtain a casting solution; then cast the casting solution on a glass plate and dry it at a certain temperature to form a film; soak the membrane in 1 mol / L potassium hydroxide solution for 24 to 48 hours, and soak it in deionized water until neutral to obtain an aryl piperidine type anion exchange membrane.
6. The preparation method according to claim 5, characterized in that: In step one, The molar concentration of N-methyl-4-piperidone in dichloromethane is 1 to 1.2 mol / L; The molar ratio of N-methyl-4-piperidone: the third monomer A: p-terphenyl is 1.1: 0.01-0.5: 0.5-0.99; The monomer A is 9,10-triphenylene, coronene, hexaphenylbenzene, spiro[fluorene-9,9'-xanthene], spiro[9H-fluorene-9,9'-[9H]thioxanthene], 5λ4-5,5'-spiro[dibenzothiophene](9CI) (CAS No.: 144190-64-7), 1,3,6,8-tetraphenylpyrene, 2,3,6,7,10,11-hexaphenyltriphenylene, 1,3-dithiazole, 2-(4,5-diphenyl-1,3-dithiol-2-ylidene)-4,5-diphenyl (CAS No.: 23780-79-2).
7. The preparation method according to claim 5, characterized in that: In step 2, The molar ratio of p-terphenyl to trifluoromethanesulfonic acid is 1:5-9; The molar ratio of p-terphenyl to trifluoroacetic acid is 1:1; The solvent B is methanol, ethanol or water.
8. The preparation method according to claim 5, characterized in that: In step three, The molar ratio of the three monomer polymer: methyl iodide: potassium carbonate is 1:1.2-1.5:1-1.5; The solvent C is N-methylpyrrolidone or dimethyl sulfoxide; The mass concentration of the three-monomer polymer in solvent C is 0.03-0.05 g / mL; The precipitation agent D is acetone, ethyl acetate or ether; The light-proof reaction time is 36 to 48 hours.
9. The preparation method according to claim 5, characterized in that: In step four, The solvent E is N-methylpyrrolidone or dimethyl sulfoxide; The mass concentration of the casting solution is 0.015-0.025 g / mL; The drying temperature of the film formed by the casting method is 60-80°C and the drying time is 24 hours.
Citation Information
Patent Citations
Anion exchange membrane containing aryl piperidine and benzenedione monomer copolymer as well as preparation method and application of anion exchange membrane
CN117510802A
Branched anion exchange membrane as well as preparation method and application thereof
CN118878789A
Poly(aryl piperidinium) polymers including those with stable cationic pendant groups for use as anion exchange membranes and ionomers
IN202047013721A
Poly(phenylene) compound intergrated with functionalized fluorene portion for anion exchange ionomer and anion exchange ionomer
WO2023081083A1
Cited By
Large steric hindrance aryl polymer, anion exchange membrane and preparation method and application thereof
CN120365535A